(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Waste is increasing rapidly in this generation. Some students irresponsibly throw their trash in proper trash bins. This study was conducted at Bestlink College of the Philippines, specifically in our classroom. Trash bins are present in our classroom, and we wonder why trash is scattered around. Even with the presence of a trash bin, if students do not have discipline, then the trash will still be scattered. That event serves as inspiration for the researchers and gives us motivation in making this study. Our study has many positive outcomes; it can reduce the amount of trash that is being thrown everywhere by the students, it can satisfy the teachers and keep their focus on teaching because they will not get irritated again because trash is being scattered, and it will make the campus clean. A descriptive method was used in this study. We used convenience sampling that is a type of nonprobability sampling method where the sample is taken from a group of people that is easy to contact or reach. Placing “ring-like” trash bins in classrooms has positive outcomes in terms of reducing garbage to be thrown by the students and innovating the students’ discipline regarding proper waste disposal. The reason for placing a “ring-like” trash bin in the classroom was to lessen the trash and help students to be responsible regard their surroundings. We conducted this study to improve the discipline of the students regarding proper waste segregation, help lessen the trash in the campus or classroom, and prevent the rapid increase in the amount of trash.